Group problem-solving skills training for self-harm: randomised controlled trial. (May 2014) - McAuliffe, Carmel; McLeavey, Breda C.; Fitzgerald, Tony; Corcoran, Paul; Carroll, Bernie; Ryan, Louise; O'Keeffe, Brian; Fitzgerald, Eva; Hickey, Portia; O'Regan, Mary; Mulqueen, Jillian; Arensman, Ella
Abstract : Background: Rates of self-harm are high and have recently increased. This trend and the repetitive nature of self-harm pose a significant challenge to mental health services. Aims: To determine the efficacy of a structured group problem-solving skills training (PST) programme as an intervention approach for self-harm in addition to treatment as usual (TAU) as offered by mental health services. Method: A total of 433 participants (aged 18–64 years) were randomly assigned to TAU plus PST or TAU alone. Assessments were carried out at baseline and at 6-week and 6-month follow-up and repeated hospital-treated self-harm was ascertained at 12-month follow-up. Results: The treatment groups did not differ in rates of repeated self-harm at 6-week, 6-month and 12-month follow-up. Both treatment groups showed significant improvements in psychological and social functioning at follow-up. Only one measure (needing and receiving practical help from those closest to them) showed a positive treatment effect at 6-week ( P = 0.004) and 6-month ( P = 0.01) follow-up. Repetition was not associated with waiting time in the PST group. Conclusions: This brief intervention for self-harm is no more effective than treatment as usual. Further work is required to establish whether a modified, more intensive programme delivered sooner after the index episode would be effective.